Natural-dye-sensitised solar cells based on TiO2 nanotube arrays. (July 2014) - Li, Na; Pan, Nengqian; Li, Xiaojing; Lin, Shiwei
<x content-type="archive" xml:space="preserve">Abstract</x> Dye-sensitised solar cells (DSSCs) were fabricated using TiO2 nanotube array photoelectrodes with natural-dye sensitizers composed of extracts of mango, pumpkin and banana. Conversion of visible light into electricity was accomplished, with a performance comparable to any that has been reported for DSSCs based on TiO2 nanoparticles. The power conversion efficiencies of cells sensitised with dyes based on mango, pumpkin and banana extracts reached 0·15%, 0·06% and 0·21%, respectively, with short-circuit current densities of 0·44, 0·13 and 0·78 mA cm−2, respectively.